Intra-operative gonioscopy: a key to successful angle surgery. (December 2014) - Shareef, Shakeel; Alward, Wallace; Crandall, Alan; Vold, Steven; Ahmed, Ike
<x xml:space="preserve">Abstract</x> Since its inception, gonioscopy has been primarily utilized for angle assessment, laser trabeculoplasty and surgery limited to the pediatric age group. Three-fourths of a century would pass since Barkan's description of goniotomy before intra-operative gonioscopy would come into vogue with the advent of micro-invasive glaucoma surgery. Over the last decade, several clinical trials have been conducted or are currently underway in evaluating devices and instruments targeting different surgical spaces within the angle. However, a rate-limiting step of successful angle surgery requires good gonioscopy and has led to a renewed interest among ophthalmologists to master this skill. During this same time period, several goniosurgical lens prototypes have been introduced in the market with the goal of optimizing angle viewing including clarity, globe stability, accessibility and simultaneous surgical manipulation of angle structures. Several non-gonioscopic methods have also been recently introduced to facilitate angle surgery.